The dynamics of covering 1 km distance in rowing and canoeing on 2009-2011 world championships - Kovalenko Stanislav Aleksandrovich; Grechuha Sergej Vasil'evich (Kharkov National Pedagogical University, 2011)
The dynamics of covering 1000 m finals was analyzed according to the protocols of 2009-2010 World Championships in rowing and canoeing. The leaders of the world rowing were found to prefer the tactics of controlling opponents at the distance. The characteristic feature for all boat types is significantly less time at the first 250-m of the distance (on 4-8%) if compared with the second and third quarters of the distance. The dynamics of covering 1000 m distance differs and depends on the boat type and individual peculiarities of the sportsmen's preparedness.